2022
DOI: 10.1037/apl0000980
|View full text |Cite
|
Sign up to set email alerts
|

The impact of leader dominance on employees’ zero-sum mindset and helping behavior.

Abstract: Leaders strive to encourage helping behaviors among employees, as it positively affects both organizational and team effectiveness. However, the manner in which a leader influences others can unintentionally limit this desired behavior. Drawing on social learning theory, we contend that a leader's tendency to influence others via dominance could decrease employees' interpersonal helping. Dominant leaders, who influence others by being assertive and competitive, shape their subordinates' cognitive schema of suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 97 publications
1
23
1
1
Order By: Relevance
“…This suggests that zero-sum beliefs may have two independent effects on help giving, suppressing people’s overall willingness to help while also shifting their preference away from autonomy-oriented help and toward dependency-oriented help. In contrast to past findings (Kakkar & Sivanathan, 2021; Sirola & Pitesa, 2017), zero-sum beliefs do not seem to dampen people’s willingness to give dependency-oriented help. Thus, depending on the type of help they are asked to give, zero-sum thinkers may be equally likely (or even more so) to help.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This suggests that zero-sum beliefs may have two independent effects on help giving, suppressing people’s overall willingness to help while also shifting their preference away from autonomy-oriented help and toward dependency-oriented help. In contrast to past findings (Kakkar & Sivanathan, 2021; Sirola & Pitesa, 2017), zero-sum beliefs do not seem to dampen people’s willingness to give dependency-oriented help. Thus, depending on the type of help they are asked to give, zero-sum thinkers may be equally likely (or even more so) to help.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, zero-sum beliefs were not related to participants’ willingness to give their colleague a complete solution to their problem, B = −.062, SE = .148, t (128) = −.422, p = .674, or prepare the presentation for them, B = .085, SE = .142, t (128) = .598, p = .551, and only marginally related to the willingness to resolve the issue for them as a one-time favor, B = .306, SE = .157, t (128) = 1.951, p = .053. Finally, replicating past findings (Kakkar & Sivanathan, 2021; Sirola & Pitesa, 2017), zero-sum beliefs predicted participants’ refusal to help, as measured by the three filler items, B = .385, SE = .100, t (128) = 3.85, p = .0002. Thus, although participants who believed that success is zero-sum were generally less willing to help their colleagues, this reluctance was only reflected in their willingness to give autonomy-oriented, but not dependency-oriented, help.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…It is possible that cultural differences based on familial social class backgrounds might play a different role in status-related judgments at work with negative outcomes. For example, other research has shown that a leader's level in behavioural dominance influences perceivers' judgments of their ambiguous moral transgressions (Kakkar et al, 2020) or team-members' zero-sum perceptions (Kakkar & Sivanathan, 2021). Future research should extend the here reported cultural differences of status-related judgments to social contexts beyond work.…”
Section: Limitations and Future Researchmentioning
confidence: 75%
“…Dominating other people. Students seek to control others by being confident and assertive about their point of view and sometimes forcing others (Kakkar & Sivanathan, 2021). 3.…”
Section: Isolated Behavior Theorymentioning
confidence: 99%